2021
DOI: 10.1016/j.idm.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climate factors on the incidence of hand, foot, and mouth disease in Malaysia: A generalized additive mixed model

Abstract: Climate change is one of the critical determinants affecting life cycles and transmission of most infectious agents, including malaria, cholera, dengue fever, hand, foot, and mouth disease (HFMD), and the recent Corona-virus pandemic. HFMD has been associated with a growing number of outbreaks resulting in fatal complications since the late 1990s. The outbreaks may result from a combination of rapid population growth, climate change, socioeconomic changes, and other lifestyle changes. However, the modeling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…8,9 Surprisingly, studies revealed that not only respiratory infectious diseases but also intestinal infectious diseases cases dramatically decreased in multiple regions during the COVID-19 pandemic. [10][11][12] This indicated that the positive effects of anti-COVID-19 measures extended to several other communicable diseases, [13][14][15] and were also confirmed in China. 16 Specifically, there was a more dramatic decline in HFMD incidence than in other intestinal infectious diseases in 2020.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…8,9 Surprisingly, studies revealed that not only respiratory infectious diseases but also intestinal infectious diseases cases dramatically decreased in multiple regions during the COVID-19 pandemic. [10][11][12] This indicated that the positive effects of anti-COVID-19 measures extended to several other communicable diseases, [13][14][15] and were also confirmed in China. 16 Specifically, there was a more dramatic decline in HFMD incidence than in other intestinal infectious diseases in 2020.…”
mentioning
confidence: 75%
“…To overcome the COVID‐19 crisis, governments worldwide implemented a series of corresponding measures using nonpharmaceutical interventions (NPIs) (e.g., home quarantine, reducing social distancing, travel restrictions, and masking), which have mitigated the magnitude and geographical scope of COVID‐19 propagation 8,9 . Surprisingly, studies revealed that not only respiratory infectious diseases but also intestinal infectious diseases cases dramatically decreased in multiple regions during the COVID‐19 pandemic 10–12 . This indicated that the positive effects of anti‐COVID‐19 measures extended to several other communicable diseases, 13–15 and were also confirmed in China 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found a correlation between climate factors and the prevalence of enterovirus infections, with several climate factors, including temperature, humidity, rainfall, wind speed, sunshine, and air pressure, being identified as important factors. For example, temperature has been widely recognized as one of the most important climate factors that affect the prevalence of enterovirus infection [ 8 , 9 , 10 , 11 ]. One study found a positive correlation between the incidence of hand, foot, and mouth disease (HFMD) and a 1 °C increase in temperature [ 8 ], while other studies showed that temperature has a delayed impact on enterovirus prevalence ranging from several days to weeks [ 9 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, temperature has been widely recognized as one of the most important climate factors that affect the prevalence of enterovirus infection [ 8 , 9 , 10 , 11 ]. One study found a positive correlation between the incidence of hand, foot, and mouth disease (HFMD) and a 1 °C increase in temperature [ 8 ], while other studies showed that temperature has a delayed impact on enterovirus prevalence ranging from several days to weeks [ 9 , 10 , 12 ]. However, some studies have found a nonlinear inverted V-shaped relationship between HFMD and temperature [ 13 ], while others have found no statistically significant correlation [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation